KURS JĘZYKA OBCEGO W ROTACJI TRANSGRANICZNEJ – OPTYMALNY CZY UTOPIJNY MODEL KSZTAŁCENIA? - Jaroszewska, Anna (Neofilolog, 2018)
Appreciating the complexity of glottodidactic system, the viability of ob-jectives as well as the multiplicity of foreign language teaching and learn-ing methods, the author of this paper attempts to form a more precise definition of a relatively new language learning concept which is the lan-guage course based on foreign exchange.